Nano-based drug delivery systems for active ingredients from traditional Chinese medicine: Harnessing the power of nanotechnology - Zhang, Yong-Bo; Wang, Jun-Fang; Wang, Mei-Xia; Peng, Jing; Kong, Xiang-De; Tian, Jie (Frontiers in Pharmacology, 2024)
Traditional Chinese medicine (TCM) is gaining worldwide popularity as a complementary and alternative medicine. The isolation and characterization of active ingredients from TCM has become optional strategies for drug development. In order to overcome the inherent limitations of these natural products such as poor water solubility and low bioavailability, the combination of nanotechnology with TCM has been explored. Taking advantage of the benefits offered by the nanoscale, various drug delivery systems have been designed to enhance the efficacy of TCM in the treatment and prevention of diseases. The manuscript aims to present years of research dedicated to the application of nanotechnology in the field of TCM, including the formulation, characteristics and therapeutic effects of nano-TCM. Additionally, the formation of carrier-free nanomedicines through self-assembly between active ingredients of TCM is summarized. Finally, the paper discusses the safety behind the application of nano-TCM and proposes potential research directions.